If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 18m + -52 = 5m Reorder the terms: -52 + 18m = 5m Solving -52 + 18m = 5m Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add '-5m' to each side of the equation. -52 + 18m + -5m = 5m + -5m Combine like terms: 18m + -5m = 13m -52 + 13m = 5m + -5m Combine like terms: 5m + -5m = 0 -52 + 13m = 0 Add '52' to each side of the equation. -52 + 52 + 13m = 0 + 52 Combine like terms: -52 + 52 = 0 0 + 13m = 0 + 52 13m = 0 + 52 Combine like terms: 0 + 52 = 52 13m = 52 Divide each side by '13'. m = 4 Simplifying m = 4
| X^3-16=0 | | -300y+100=500 | | -300+100=500 | | 3x=2x-5x+9 | | 3-y=10 | | -6x+3y=-12 | | 5+2x-8-6x=3x+11 | | -6x+6y=6 | | 9n+1=6n+9 | | 3x^2-17x=0 | | -98-8x=9x+21 | | 11-9x=33-16x | | x^2-4x=-29 | | 106-6x=30x+22 | | 0=.173t+.152t^2-.035t^3 | | 2k*2k= | | 4x+17=8x+5 | | 56n^2+63n=0 | | 2f+3g-f+4g= | | 3x^2+16x=12 | | 4v+3=7v-9 | | 5x-3(-3)=15 | | 5v+3=6v-9 | | 12f+2-5=69 | | 2p+-5p=30 | | 3+6x=69 | | 2z+5z=14 | | 2z+5x=14 | | x(x+4)= | | 9x^2+11x-14= | | 9-2x=21 | | 8x^2-39x+10=0 |